GALNT14 Genotype Predicts Postoperative Outcome of Stage III Colorectal Cancer With Oxaliplatin as Adjuvant Chemotherapy. Issue 17 (April 2016) - Lin, Wey-Ran; Chiang, Jy-Ming; Liang, Kung-Hao; Lim, Siew-Na; Lai, Ming-Wei; Tsou, Yung-Kuan; Hsieh, Tzu-Yun; Hsu, Chih-Kai; Yeh, Chau-Ting
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Adjuvant oxaliplatin-based chemotherapy is widely used for stage III colorectal cancer (CRC) after curative surgery. CRC is a molecularly heterogeneous disease, and our current knowledge of therapeutic response-related genetic factors remains limited. N -acetylgalactosaminyltransferase 14 ( GALNT14 )-rs9679162 genotype is a prognostic predictor for chemotherapy response in advanced hepatocellular carcinoma. Here, we investigated whether this genotype was related to the therapeutic outcome of stage III CRC. A cohort of 300 stage III CRC patients receiving curative resection followed by oxaliplatin-based chemotherapy was retrospectively recruited. GALNT14 genotypes and the clinicopathological factors were correlated with posttherapeutic prognosis. Of these patients, 18% patients had GALNT14 -rs9679162 "TT" and 82% had the "GT" + "GG" genotypes. The analysis showed that the "TT" genotype was associated with unfavorable overall survival (OS, P = 0.009) but not with recurrence-free survival (RFS, P = 0.700). The subgroup analysis showed that the "TT" genotype was associated with unfavorable OS in the following subgroups: age ≤65 years, men, left side CRC, N2 stage, carcinoembryonic antigen >5 ng/mL, and mucinous histology ( P = 0.012, 0.011, 0.009, 0.025, 0.013, and 0.007, respectively). Within the latter 2 subgroups, the "TT" genotype was the only independent predictor for OS. Finally, the "TT" genotype was associated with the T4 tumor stage ( P = 0.017) and in patients with T4 tumors, the "TT" genotype was the only independent predictor for unfavorable RFS ( P = 0.007). GALNT14 "TT" genotype was associated with unfavorable OS in stage III CRC patients receiving curative surgery and adjuvant oxaliplatin-based chemotherapy.